Pengaruh Penilaian Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Perum Perhutani KPH Kota Probolinggo - Ahmad Basofi Ramadan; Yayuk Indah Wahyuning Tyas; Dyah Ayu Perwitasari (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
Basically, companies make human resources an important factor in the sustainability of the company and make them play a fairly efficient role in every activity in the company. One of them is performance, which plays an important role in the company to achieve profits. From the results of good performance, positive opportunities are obtained. This type of research uses an associative quantitative approach. The sampling technique used was a saturated sampling technique, so the total sampling number of all Perum Perhutani KPH employees in the city of Probolinggo was 74 employees. The source of data Z that is used is obtained from primary data and secondary data. From the results of the job assessment test) and career development have a simultaneous effect on employee performance. Meanwhile, from the partial test results it was found that the work assessment variable had a significant influence on employee performance. And the career development variable partially influences employee performance.